Household Income Mobility in India: 1993-2011 - Mehtabul Azam (Institute for the Study of Labor (IZA), 2016)
Using nationally representative longitudinal survey, we examine the income mobility among rural (urban) Indian households over 1993-2004 and 2004-2011 (2004-2011). We find mobility estimates that mirror the social hierarchy: Forward Hindu Caste (FHC) households experienced the highest (lowest) upward (downward) mobility. Considerable gaps between FHC households and households from the disadvantaged social groups remain in upward/downward mobility even after controlling for households characteristics. We find lower conditional gaps in both upward/downward mobility in rural India for the disadvantaged groups (except for Muslims) over 2004-2011 compared to 1993-2004. For Muslims, the gaps in downward mobility increased over 2004-11 compared to 1993-2004.
Keywords: O15; D31; I32; 330; intragenerational; income mobility; social groups; scheduled castes/tribes; India